Endophytic Fungi from Salt Adapted Plants Confer Salt Tolerance in Barley - Rabiaa Kouadria; Mohammed Bouzouina; Brahim Lotmani (Tunisian Journal of Plant Protection, 2023)
Kouadria, R., Bouzouina, M., and Lotmani, B. 2023. Endophytic fungi from salt adapted plants confer salt tolerance in barley. Tunisian Journal of Plant Protection 18 (2): 63-70.